Synergistic effects of fly ash as filler on the mechanical and durability properties of recycled concrete aggregates solid masonry blocks - Md Mohsin M Dafedar; Kiran K Shetty; Balakrishna Rao K; B.H. Venkataram Pai; Gopal Bharamappa Bekkeri (European Journal of Environmental and Civil Engineering, 2026)

Multi-event temporal assessment of urban flood hazard and risk in Hyderabad, integrating GIS-based multi-criteria analysis, statistical linkages, and machine-learning robustness evaluation - Ravali Bharadwaj; Harish Gupta; Aadhi Naresh; M. Gopal Naik; Srinivasulu Ale; Fouad H Jaber (Environment, Development and Sustainability, 2026)

Distribution and Ecological Risk of Microplastics Across Air, Water, and Soil in a Coastal Megacity of Southern India - M. Bhuvaneswari; Anju Maria Joseph; S. Yamini; M. Suresh Gandhi; V. Gopal (Water, Air, & Soil Pollution, 2026)

Microplastic contamination in locally and industrially produced organic fertilizers: Implications for sustainable agriculture and risk mitigation - Mahfuz Ahmmed; Md Hasibuzzaman; Ismail M. Rahman; Sadia Sultana Mitu; Tapos Kumar Chakraborty; Gopal Chandra Ghosh (Chemosphere, 2026)

Elucidating the molecular basis of Streptomyces antifungal activity against Fusarium verticillioides, causing maize ear and stalk rot pathogen - K.N. Pallavi; M.K. PrasannaKumar; J. Harish; R. Karan; Gopal Venkateshbabu; M. Nithish; C. Manjunatha; Deepaka; Swathi S. Patil; Aditya Narayan Sarangi (Biocatalysis and Agricultural Biotechnology, 2026)

Integrated experimental, statistical, and ANN validation study on concrete deterioration under acid rain, carbonation, and chloride environments - Y. H. Sudeep; V. Vijaykumar; M. S. Ujawl; Christo George; S. Karthik; Rakesh Kumar; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2026)
Concrete structures in coastal–industrial regions are simultaneously exposed to acid rain, carbonation, and chloride ingress; however, most durability studies investigate these mechanisms independently, limiting realistic service-life prediction. This study presents an integrated experimental, statistical, and artificial neural network (ANN)-based evaluation of M40-grade concrete subjected to synthetic acid rain, accelerated carbonation, and combined carbonation–chloride environments. Laboratory simulations were conducted for exposure durations of 20, 40, 60, and 80 h to replicate aggressive atmospheric conditions. Mechanical degradation was assessed through compressive and splitting tensile strength tests, while chemical deterioration was quantified using depth-wise pH profiling and carbonation depth measurements. Results revealed that compressive strength decreased by up to ~ 25% under acid rain exposure and showed greater deterioration under combined carbonation–chloride conditions. Splitting tensile strength exhibited higher sensitivity to degradation, with reductions exceeding 20% at prolonged exposure durations. Surface pH declined from 12.6 to approximately 8.8, confirming rapid alkalinity loss in the outer 1 cm zone. Carbonation depth increased progressively, reaching ~ 11.5 mm in the combined exposure environment. Regression analysis demonstrated strong inverse correlations (R 2 > 0.90) between carbonation depth and mechanical properties, while one-way ANOVA confirmed statistically significant differences across exposure durations ( p < 0.05). To enhance predictive capability, an ANN model was developed using experimental parameters as inputs, achieving high prediction accuracy (R 2 = 0.98 for training and R 2 = 0.96 for testing). The findings highlight synergistic deterioration effects of multi-environmental exposure and emphasize durability-based design strategies for reinforced concrete structures in aggressive environments.

Soil moisture estimation using Sentinel-1 SAR and field observation in the Eastern Ghats region of India - Uday Mandal; M. Madhu; Ramajayam Devarajan; Randhir Kumar; Gopal Kumar; HC Hombegowda; SK Samal; Saswat Kumar Kar; P. Raja; Pyla Sravani; Sitanshu Sekhar Patra (Environmental Monitoring and Assessment, 2026)

Radon-thoron exhalation rates in mineral-enriched beach sand of the Chennai coast, India - M. John Samson; K. Manikanda Bharath; A. Vidyasakar; K. Ajith Kumar; V. Arun Bharathi; Satyanarayan Bramha; S. Chandrasekaran; Kannaiyan Neelavannan; V. Gopal; S. Ajith Kumar; N. Sivakumar (Environmental Geochemistry and Health, 2026)

Atmospheric microplastics deposition in Dhaka City, Bangladesh: occurrence, distribution and ecological risk assessment - Md Tauhiduzzaman; Nishat Salsabil; Kobita Khatun; Md Muhaiminul Haque; Ahsan Habib; Mst Shamima Akter; Sojib Islam; Md Hasibuzzaman; Ismail M. Rahman; Mahfuz Ahmmed; Samina Zaman; Tapos Kumar Chakraborty; et al. (Atmospheric Pollution Research, 2026)

Taming Light with Carbon Dots - Arun M; Karthikeyan Alagarsamy; T. C. Sabri Girisun; Kannan Prabha; Murugan Perumal; Archana Pandi; Ramalingam Gopal (Journal of Fluorescence, 2026)

Demystifying the association of the gut–TMAO–heart axis: focusing on gut microbiota in myocardial infarction - Krushna Ch Maharana; Mayuri Adsule; M Rajkumar; Gopal Vishwas; Sanjiv Singh (Next Research, 2026)

Tracing surface-adhered and internalized microplastics in leafy vegetables across urban and rural agroecosystems: Occurrence, characteristics, pollution indices, and exposure assessment - Ismail M. Rahman; Gopal Chandra Ghosh; Sadia Sultana Mitu; Mahfuz Ahmmed; Md Hasibuzzaman; Danisha Sultana; Jarin Tasnim Asha; Sojib Islam; Md. Tauhiduzzaman; Tapos Kumar Chakraborty; Samina Zaman; Seiya Hanamoto; et al. (Journal of Hazardous Materials, 2026)

Degraded land: Assessment, impact, restoration, and challenges - Gulshan Kumar Sharma; Dinesh Jinger; I. Rashmi; Manoj Kumar; Nandha Kumar Natrajan; Roomesh Kumar Jena; Raj Kumar; Suresh Kumar; Kavita Kumari; Rajesh Kaushal; Anupam Barh; Trisha Roy; et al. (Journal of Environmental Management, 2026)

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bioaccumulation of elements in the edible part of vegetables from the agricultural soil: Source apportionment and potential risks - Rahat Khan; Md Samium Basir; Narottam Saha; Kazi Anisur Rahman; Md Tazul Islam; Goshtha Gopal Biswas; Abubakr M. Idris; Md Harunor Rashid Khan; Saad Aldawood (Journal of Environmental Management, 2025)

Optimization of parameters for the HEC-HMS model based on real-time flow monitoring data: a case study of Hyderabad metropolitan area, India - Naresh Aadhi; Ravali Bharadwaj; M. Gopal Naik; Harish Gupta; Fouad H Jaber; Srinivasulu Ale (Modeling Earth Systems and Environment, 2025)

A coral microatoll record of sea-level rise, interseismic deformation, and El Niño in La Union, Philippines since 1906 CE - Gina M. Sarkawi; Aron J. Meltzner; Dongju Peng; Joanne T.Y. Lim; Xinnan Li; Rohan Gautam; Anandh Gopal; Andrew Mitchell; Loraine Faye Sarmiento; Jennifer Weil-Accardo; Kathrine V. Maxwell; Junki Komori; et al. (Marine Geology, 2025)

The Human Shield Hypothesis: Does Predator Avoidance of Humans Create Refuges for Prey? - Kaitlyn M. Gaynor; Eamonn I. F. Wooster; April Robin Martinig; Jennifer R. Green; Aimee Chhen; Sandra Cuadros; Ryan Gill; Gopal Khanal; Nicola Love; Rekha Marcus; C. Lauren Mills; Kwasi Wrensford; et al. (Ecology Letters, 2025)
As anthropogenic disturbance restructures ecological communities worldwide, ecologists have developed and tested hypotheses about which species “win” and “lose” in the face of human impacts. One heavily invoked paradigm is that of the human shield, which posits that predators avoid areas of human disturbance due to perceived risk from humans, and prey therefore seek refuge in these areas of perceived safety. Since its introduction in 2007, the human shield hypothesis (HSH) has gained popularity in the ecological literature, although there are more passing mentions of human shields than there are robust tests of the HSH. Here, we systematically review evidence for the HSH and evaluate how it is commonly discussed and tested. While there are several clear‐cut cases of human shields, the emergence of human shields is highly context‐dependent. By formally outlining the assumptions of the HSH, we derive predictions about what ecological and anthropogenic contexts are most likely to be conducive to human shields. Further robust studies that compete the HSH against alternative hypotheses and account for confounding factors can shed light on the role of human shields in human‐modified ecosystems and inform the conservation and management of wildlife in a changing world.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Molecular virulotyping and advancing the detection of Magnaporthe oryzae using a CRISPR-Cas12a-based diagnostic tool - R. Karan; M. K. Prasannakumar; Harvinder Kour Khera; J. Harish; N. Vamsidharreddy; Gopal Venkateshbabu; Pramesh Devanna; C. Manjunatha; K. B. Palanna; Rakesh Kumar Mishra (World Journal of Microbiology and Biotechnology, 2025)

Fatigue performance and thickness optimization of polyolefin fiber-reinforced M40 concrete for sustainable pavements - J. C Vidyashree; E. K Reshma; M. Harshitha; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2025)
Concrete pavements are renowned for their ability to handle heavier loads and lower life cycle costs than flexible pavements. Fibers into concrete further enhance its durability by reducing maintenance and rehabilitation costs. This study investigates the fatigue performance of pavement quality concrete (PQC) M40-grade reinforced with polyolefin fibers, focusing on structured fibers (SF) and twisted fibers (TF). Polyolefin fibers were added at varying dosages (0.8, 0.9, and 1.0 kg/m³ for structured fibers and 3, 4, and 5 kg/m³ for twisted fibers), as per IRC: 44 (2017) guidelines. Tests were conducted for compressive, split tensile, flexural strength, and flexural fatigue under different stress levels and loading frequencies. Results revealed that polyolefin fibers significantly improve concrete’s mechanical properties and fatigue resistance. Optimal dosages were identified as 1 kg/m³ for structured fibers and 5 kg/m³ for twisted fibers. The S-N curves demonstrated enhanced durability under cyclic loading conditions. Furthermore, polyolefin fiber reinforcement reduced white topping thickness from 19 cm to 17 cm while maintaining flexural stress within safe limits. This optimization highlights the potential for more durable, cost-effective, and sustainable pavement solutions.

Distribution and characterization of phytoplasmas infecting flower crops with diverse symptoms in Andhra Pradesh State, India - D. Meghanath; K. Arunodhayam; M. Gurivi Reddy; Ch. Ruth; M. Raja Naik; K. Gopal (Australasian Plant Pathology, 2025)

Conservation tillage-based Arundo donax agro-geotextiles enhance productivity and profitability of sloping croplands in the Indian Himalayas by reducing soil erosion and improving soil organic carbon - Raman Jeet Singh; Gopal Kumar; N.K. Sharma; J.S. Deshwal; Mudit Mishra; Plabani Roy; Ranjan Bhattacharyya; M. Madhu (Journal of Environmental Management, 2025)

3-Hydroxybenzoic acid inhibits the virulence attributes and disrupts biofilm production in clinical isolates of Acinetobacter baumannii - Naji Naseef Pathoor; Pitchaipillai Sankar Ganesh; Abdul R. Anshad; Rajesh Kanna Gopal; Esaki Muthu Ponmalar; Suvaiyarasan Suvaithenamudhan; Parthiban Rudrapathy; Esaki M. Shankar (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Pleural Fluid Calprotectin Levels in Benign and Malignant Pleural Effusions and Its Significance in Predicting Success of Pleurodesis in Malignant Pleural Effusions - Amartya Chakraborti; Nishant Kumar Chauhan; Naveen Dutt; Mithu Banerjee; Ravisekhar Gadepalli; Deepak Vedant; M. K. Garg; Gopal Durgeshwar; Hariharan Iyer (Indian Journal of Clinical Biochemistry, 2025)

Evaluation of the engineering properties and sustainability of solid masonry blocks produced with recycled concrete aggregates - Md Mohsin M. Dafedar; K. Balakrishna Rao; B. H. Venkataram Pai; Gopal Bharamappa Bekkeri (Innovative Infrastructure Solutions, 2024)
The rapid expansion of global infrastructure has led to significant natural resource shortages and increasing environmental concerns related to construction and demolition (C&D) waste. Recycling C&D waste presents a viable solution to alleviate resource depletion and promote sustainability. This study explores the use of recycled concrete aggregates (RCAs) derived from C&D waste in producing solid masonry blocks (SMBs). RCAs were employed to replace both natural coarse and fine aggregates in these blocks. Physical and mechanical properties of SMBs were tested, including hardened density, compressive and flexural strengths, and water absorption. The findings showed that decreased strength and increased water absorption for cement-to-aggregate ratio (C: A) increased from 1:6 to 1:24; however, all produced SMBs satisfied the requirements specified by Indian and ASTM standards. The study concluded that using 100% RCAs in SMBs is structurally sound and environmentally beneficial, meeting international standards. Employing recycled aggregate concrete blocks lowers environmental impact and aids in sustainable development by facilitating the life-cycle closure of the building materials.

Extreme rainfall storm-induced surface runoff and sediment dynamics of conservation tillage-based agro-geotextiles emplaced on sloping croplands of the Indian Himalayan Region - Raman Jeet Singh; Gopal Kumar; N.K. Sharma; J.S. Deshwal; M. Madhu (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Assessing the elevational relationship with soil physico-chemical properties under traditional large cardamom agroforestry system in the Indian Eastern Himalayas: a case study using machine learning algorithms - Vineeta; Biplov Ch. Sarkar; M. Tamang; Gopal Shukla; M. K. Debnath; Amitabha Nath; Arun Jyoti Nath; Sumit Chakravarty (Environment, Development and Sustainability, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Paradigm of integrative OMICS of microbial technology towards biorefinery prospects - Samuel Jacob; Gunasekaran Rajeswari; Awantika Rai; Sushree Shweta Tripathy; Swathy Gopal; Eeshita Das; Vinod Kumar; S.P. Jeevan Kumar; Tejraj M. Aminabhavi; Vijay Kumar Garlapati (Biocatalysis and Agricultural Biotechnology, 2024)

Stalk rot species diversity and molecular phylogeny associated with diseased maize in India - J. Harish; Gopal Venkateshbabu; M. K. Prasannakumar; Pramesh Devanna; H. B. Mahesh; D. C. Balasundara; S. Dharanendra Swamy; Sridhara G. Kunjeti; C. Manjunatha; M. E. Puneeth; H. C. Lohithaswa; Prashant P. Jambhulkar (World Journal of Microbiology and Biotechnology, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Wound healing activities of PVA–urea composites from Ormocarpum cochinchinense - N. Aarthi; M. Muthuraj; M. Archana; V. Gopal; N. Balasubramanian; S. Rajeswari (Natural Product Research, 2024)

Low Ionosphere Density Above the Earthquake Epicentre Region of Mw 7.2, El Mayor–Cucapah Earthquake Evident from Dense CORS Data - Gopal Sharma; Karan Nayak; Rosendo Romero-Andrade; M. A. Mohammed Aslam; K. K. Sarma; S. P. Aggarwal (Journal of the Indian Society of Remote Sensing, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Correction to: Evaluation of the Global Ensemble Forecast System (GEFS T1534) for the probabilistic prediction of cyclonic disturbances over the North Indian Ocean during 2020 and 2021 - Radhika Kanase; Snehlata Tirkey; Medha Deshpande; R Phani Murali Krishna; C J Johny; P Mukhopadhyay; Gopal Iyengar; M Mohapatra (Journal of Earth System Science, 2023)

Plant-microbe interaction mediated salinity stress tolerance for sustainable crop production - Ritu Sharaya; Ritu Gill; Gopal Kalwan; M. Naeem; Narendra Tuteja; Sarvajeet Singh Gill (South African Journal of Botany, 2023)

Correction to: New Records of Polychaetes from Palk Bay, Bay of Bengal, Northern Indian Ocean - Aiswarya Gopal; Jawed Equbal; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Thalassas: An International Journal of Marine Sciences, 2023)

New Records of Polychaetes from Palk Bay, Bay of Bengal, Northern Indian Ocean - Aiswarya Gopal; Jawed Equbal; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Thalassas: An International Journal of Marine Sciences, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Corrigendum to addresses “Effective biocontrol of banana fusarium wilt tropical race 4 by a bacillus rhizobacteria strain with antagonistic secondary metabolites” [Rhizosphere 18 (2021) 100341] - Kavita Yadav; T. Damodaran; Kakoli Dutt; Arjun Singh; M. Muthukumar; S. Rajan; Ram Gopal; P.C. Sharma (Rhizosphere, 2023)

Evaluation of the Global Ensemble Forecast System (GEFS T1534) for the probabilistic prediction of cyclonic disturbances over the North Indian Ocean during 2020 and 2021 - Radhika Kanase; Snehlata Tirkey; Medha Deshpande; R Phani Murali Krishna; C J Johny; P Mukhopadhyay; Gopal Iyengar; M Mohapatra (Journal of Earth System Science, 2023)

Integration of Biorelevant Pediatric Dissolution Methodology into PBPK Modeling to Predict In Vivo Performance and Bioequivalence of Generic Drugs in Pediatric Populations: a Carbamazepine Case Study - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Abdullah Al Shoyaib; Marie-Christine Jones; Hannah K. Batchelor (The AAPS Journal, 2023)
This study investigated the impact of gastro-intestinal fluid volume and bile salt (BS) concentration on the dissolution of carbamazepine (CBZ) immediate release (IR) 100 mg tablets and to integrate these in vitro biorelevant dissolution profiles into physiologically based pharmacokinetic modelling (PBPK) in pediatric and adult populations to determine the biopredictive dissolution profile. Dissolution profiles of CBZ IR tablets (100 mg) were generated in 50–900 mL biorelevant adult fasted state simulated gastric and intestinal fluid (Ad-FaSSGF and Ad-FaSSIF), also in three alternative compositions of biorelevant pediatric FaSSGF and FaSSIF medias at 200 mL. This study found that CBZ dissolution was poorly sensitive to changes in the composition of the biorelevant media, where dissimilar dissolution (F2 = 46.2) was only observed when the BS concentration was changed from 3000 to 89 μM (Ad-FaSSIF vs Ped-FaSSIF 50% 14 BS). PBPK modeling demonstrated the most predictive dissolution volume and media composition to forecast the PK was 500 mL of Ad-FaSSGF/Ad-FaSSIF media for adults and 200 mL Ped-FaSSGF/FaSSIF media for pediatrics. A virtual bioequivalence simulation was conducted by using Ad-FaSSGF and/or Ad-FaSSIF 500 mL or Ped-FaSSGF and/or Ped-FaSSIF 200 mL dissolution data for CBZ 100 mg (reference and generic test) IR product. The CBZ PBPK models showed bioequivalence of the product. This study demonstrates that the integration of biorelevant dissolution data can predict the PK profile of a poorly soluble drug in both populations. Further work using more pediatric drug products is needed to verify biorelevant dissolution data to predict the in vivo performance in pediatrics. Graphical Abstract

Famished Frugivores or Choosy Consumers: A Generalist Frugivore (Wild Bornean Orangutans, Pongo pygmaeus wurmbii) Leaves Available Fruit for Nonfruit Foods - Andrea L. DiGiorgio; Yaxiong Ma; Elizabeth M. Upton; Sucharita Gopal; Natalie J. Robinson; TriWahyu Susanto; Cheryl D. Knott (International Journal of Primatology, 2023)

Integrated approach for the investigation of groundwater quality through hydrochemistry and water quality index (WQI) - Gopal Krishan; Mohit Kumar; M. Someshwar Rao; Rahul Garg; Brijesh Kumar Yadav; M.L. Kansal; Surjeet Singh; A. Bradley; Marian Muste; L.M. Sharma (Urban Climate, 2023)

Ecohydrological, climatic and tree architectural considerations for reforestation program using swamp vegetation of Bangladesh - Md. Shawkat Islam Sohel; H. M. Nurul Islam; Kazi Md. Noor Newaz; Malik Fida A. Khan; Gopal Chandra Sarker; Md. Sadequr Rahman Bhuiyan (Ecohydrology & Hydrobiology, 2023)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Autochthonous nutrient recycling driven by soil microbiota could be sustaining high coconut productivity in Lakshadweep Islands sans external fertilizer application - Murali Gopal; Alka Gupta; V. Arunachalam; H. P. Maheswarappa; George V. Thomas; P. M. Jacob (World Journal of Microbiology and Biotechnology, 2022)

Mass balance estimation of Mulkila glacier, Western Himalayas, using glacier melt model - Geetha Priya M.; Chandhana Guruprasad; Deeksha Gopal; Suresh Devaraj (Environmental Monitoring and Assessment, 2022)

Optimal selection of representative climate models and statistical downscaling for climate change impact studies: a case study of Rhode Island, USA - Shiva Gopal Shrestha; Soni M. Pradhanang (Theoretical and Applied Climatology, 2022)

Exosomes as cell-derivative carriers in the diagnosis and treatment of central nervous system diseases - Gayatri Gopal Shetgaonkar; Shirleen Miriam Marques; Cleona E. M. DCruz; R. J. A. Vibhavari; Lalit Kumar; Rupesh Kalidas Shirodkar (Drug Delivery and Translational Research, 2022)
Exosomes are extracellular vesicles with the diameter ranging from 50 to 100 nm and are found in different body fluids such as blood, cerebrospinal fluid (CSF), urine and saliva. Like in case of various diseases, based on the parent cells, the content of exosomes (protein, mRNA, miRNA, DNA, lipids and metabolites) varies and thus can be utilized as potential biomarker for diagnosis and prognosis of the brain diseases. Furthermore, utilizing the natural potential exosomes to cross the blood–brain barrier and by specifically decorating it with the ligand as per the desired brain sites therapeutics can be delivered to brain parenchyma. This review article conveys the importance of exosomes and their use in the treatment and diagnosis of brain/central nervous system diseases. Graphical abstract

Evaluation of Physicochemical Characteristics of Coastal Waters of Nellore, Southeast Coast of India, by a Multivariate Statistical Approach - Krupa Ratnam; Dilip Kumar Jha; M. Prashanthi Devi; Gopal Dharani (Frontiers in Marine Science, 2022)
The Swarnamukhi river estuary (SRE), and the surrounding sea in Nellore, southeast coast of India, is one of the least studied marine environments, notably for physicochemical characteristics. Seawater samples were collected from five stations every month from 2014 to 2017 to assess physicochemical characteristics. The open sea (OS) station was significantly different from the inner stations, according to non-metric multidimensional scaling and cluster analysis. The variability was shown by strong factor loadings of atmospheric temperature (0.87), water temperature (0.84), biochemical oxygen demand (0.77), ammonia (0.85), and total nitrogen (0.78). Furthermore, one-way ANOVA and box-whisker plots facilitated simplifying and corroborating multivariate results that showed high concentration in the inner stations. Based on the N/P and Si/N ratios, nitrate and silicate were the key limiting factors in this study. The findings are critical for establishing reference conditions for comparison studies with other comparable ecosystems in the tropical region for better environmental conservation and management.

High-Frequency Concurrent Measurements in Watershed and Impaired Estuary Reveal Coupled DOC and Decoupled Nitrate Dynamics - Gopal K. Mulukutla; Wilfred M. Wollheim; Joseph E. Salisbury; Richard O. Carey; Thomas K. Gregory; William H. McDowell (Estuaries and Coasts, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Diversity and biopotential of Bacillus velezensis strains A6 and P42 against rice blast and bacterial blight of pomegranate - Siddulakshmi Prasanna; M. K. Prasannakumar; H. B. Mahesh; Gopal Venkatesh Babu; P. Kirnaymayee; M. E. Puneeth; Karthik S. Narayan; D. Pramesh (Archives of Microbiology, 2021)

Comparative Evaluation of Patties Prepared from Pacific White Shrimps ( Litopenaeus vannamei ) Grown in Inland Saline Water and Brackish Water Regimes during Frozen Storage - D M Affarin Tinku; K.A. Martin Xavier; Binaya Bhushan Nayak; V. Hari Krishna; Gopal Krishna; Amjad Khansaheb Balange (Journal of Aquatic Food Product Technology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Design, Development, In Vitro and Preliminary In Vivo Evaluation of a Novel Photo-Angioplasty Device: Lumi-Solve - HongBin Liu; Gopal R. Sama; Andrea Robinson; Simon Mountford; Philip E. Thompson; Andrew Rodda; John Forsythe; Patrick J. Mornane; Paul Pasic; Helmut Thissen; Melissa Byrne; David M. Kaye; et al. (Cardiovascular Engineering and Technology, 2021)

Development of a Pediatric Relative Bioavailability/Bioequivalence Database and Identification of Putative Risk Factors Associated With Evaluation of Pediatric Oral Products - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Franci Naumann; Hannah K. Batchelor (The AAPS Journal, 2021)
Generally, bioequivalence (BE) studies of drug products for pediatric patients are conducted in adults due to ethical reasons. Given the lack of direct BE assessment in pediatric populations, the aim of this work is to develop a database of BE and relative bioavailability (relative BA) studies conducted in pediatric populations and to enable the identification of risk factors associated with certain drug substances or products that may lead to failed BE or different pharmacokinetic (PK) parameters in relative BA studies in pediatrics. A literature search from 1965 to 2020 was conducted in PubMed, Cochrane Library, and Google Scholar to identify BE studies conducted in pediatric populations and relative BA studies conducted in pediatric populations. Overall, 79 studies covering 37 active pharmaceutical ingredients (APIs) were included in the database: 4 bioequivalence studies with data that passed BE evaluations; 2 studies showed bioinequivalence results; 34 relative BA studies showing comparable PK parameters, and 39 relative BA studies showing differences in PK parameters between test and reference products. Based on the above studies, common putative risk factors associated with differences in relative bioavailability (DRBA) in pediatric populations include age-related absorption effects, high inter-individual variability, and poor study design. A database containing 79 clinical studies on BE or relative BA in pediatrics has been developed. Putative risk factors associated with DRBA in pediatric populations are summarized.

Management of Fusarium root rot of coriander with chemical and bio‐control agents - M. S. V. Satyanarayana; K. Gopal; Ch. Ruth; S. Sadarunnisa; V. Vijaya Bhaskar (Indian Phytopathology, 2021)

Rapid genotyping of bacterial leaf blight resistant genes of rice using loop-mediated isothermal amplification assay - M. K. Prasannakumar; Buela P. Parivallal; Chennappa Manjunatha; Devanna Pramesh; Karthik S. Narayan; Gopal Venkatesh; Sahana N. Banakar; H. B. Mahesh; Ramu S. Vemanna; K. T. Rangaswamy (Molecular Biology Reports, 2021)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Measured and predicted acute toxicity of phenanthrene and MC252 crude oil to vertically migrating deep-sea crustaceans - Nicholas R. Turner; Gopal Bera; D. Abigail Renegar; Tamara M. Frank; Bernhard M. Riegl; José L Sericano; Stephen Sweet; Anthony H. Knap (Environmental Science and Pollution Research, 2020)

Defect minimized Ag-ZnO microneedles for photocatalysis - Sanjay Gopal Ullattil; M. J. Jabeen Fatima; Ahmed Abdel-Wahab (Environmental Science and Pollution Research, 2020)
A facile solution processing strategy has been developed for the formation of Ag-modified ZnO microneedles at various calcination temperatures such as 300, 500, and 700 °C (AZ3, AZ5, and AZ7 respectively). Due to the heavy doping of AgNO 3 , Ag + ions have been incorporated in to the crystal lattice of ZnO in all the Ag-ZnO samples, which facilitated the formation of Ag-ZnO microneedle morphology with minimized defect states, and obviously, the plasmon peaks were observed due to Ag modification. These Ag-ZnO microneedle structures have been evaluated for their photocatalytic performance using methylene blue as model target contaminant and their activity was compared with the commercially available titania P25 photocatalyst. The photoactivity of all the Ag-ZnO microneedle structures was significantly higher than that of the commercially available P25 photocatalyst with the most active Ag-ZnO material having a photocatalytic activity ~ 1.4 times greater than that of P25 titania.

Distinctive Community Patterns With Exceptional Diversity of Polychaetes Around a Tectonically Active Archipelago in the Tropical Indian Ocean - Aiswarya Gopal; K. U. Abdul Jaleel; Usha V. Parameswaran; V. N. Sanjeevan; A. V. Saramma; Anilkumar Vijayan; N. Saravanane; G. V. M. Gupta; M. Sudhakar (Frontiers in Marine Science, 2020)

Building sustainability in the Eastern Himalaya: linking evidence to action - Sandeep Tambe; Gopal S. Rawat; Nima Tashi Bhutia; Pem Norbu Sherpa; Subash Dhakal; Sarika Pradhan; Himanshu Kulkarni; M. L. Arrawatia (Environment, Development and Sustainability, 2020)

Correction to: Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Outcomes and prognostic factors for women with breast cancer in Malawi - Victoria M. Youngblood; Ruth Nyirenda; Richard Nyasosela; Takondwa Zuze; Yi Yang; Evaristar Kudowa; Agnes Moses; Jennifer Kincaid; Chifundo Kajombo; Coxcilly Kampani; Fred Chimzimu; Maurice Mulenga; et al. (Cancer Causes & Control, 2020)

Development of indices for surface and ground water quality assessment and characterization for Indian conditions - Surjeet Singh; N. C. Ghosh; Gopal Krishan; Sumant Kumar; Suman Gurjar; M. K. Sharma (Environmental Monitoring and Assessment, 2019)

An updated checklist of echinoderms of the southeastern Arabian Sea - Usha V. Parameswaran; V. N. Sanjeevan; K. U. Abdul Jaleel; Vinu Jacob; Aiswarya Gopal; Anil Kumar Vijayan; M. Sudhakar (Marine Biodiversity, 2018)

Hyperspectral satellite data analysis for pure pixels extraction and evaluation of advanced classifier algorithms for LULC classification - Gopal Krishna; Rabi N. Sahoo; Sanatan Pradhan; Tauqueer Ahmad; Prachi M. Sahoo (Earth Science Informatics, 2018)

High intraspecific genetic divergence in the versatile fairy shrimp Branchinecta lindahli with a comment on cryptic species in the genus Branchinecta (Crustacea: Anostraca) - Andres Aguilar; Alejandro M. Maeda-Martínez; Gopal Murugan; Hortencia Obregón-Barboza; D. Christopher Rogers; Kelly McClintock; Janice L. Krumm (Hydrobiologia, 2017)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Citrus yellow mosaic badnavirus infecting Citrus sp.: a threat to the citrus industry and a quarantine issue - A. M. Anthony Johnson; D. V. R. Sai Gopal; Chinta Sudhakar; Indranil Dasgupta (Journal of General Plant Pathology, 2017)

A New Fluorescent Sensor Based on Bisindolizine Derivative - Anitha I; Sheela Gopal M; Divya Thomas (Journal of Fluorescence, 2016)

Geochemical study of core sediments from Ennore Creek, North of Chennai, Tamil Nadu, India - V. Gopal; G. Kalpana; S. Nethaji; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Evaluation of total trace metal (TTMs) enrichment from estuarine sediments of Uppanar, southeast coast of India - G. Kalpana; A. Shanmugasundharam; S. Nethaji; Arya Viswam; R. Kalaivanan; V. Gopal; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Chronic hepatitis C virus infection triggers spontaneous differential expression of biosignatures associated with T cell exhaustion and apoptosis signaling in peripheral blood mononucleocytes - Muttiah Barathan; Kaliappan Gopal; Rosmawati Mohamed; Rada Ellegård; Alireza Saeidi; Jamuna Vadivelu; Abdul W. Ansari; Hussin A. Rothan; M. Ravishankar Ram; Keivan Zandi; Li Y. Chang; Ramachandran Vignesh; et al. (Apoptosis, 2015)

Ultraviolet and 5′Fluorodeoxyuridine Induced Random Mutagenesis in Chlorella vulgaris and Its Impact on Fatty Acid Profile: A New Insight on Lipid-Metabolizing Genes and Structural Characterization of Related Proteins - Josephine Anthony; Vijaya Raghavan Rangamaran; Dharani Gopal; Kumar T. Shivasankarasubbiah; Mary Leema J. Thilagam; Magesh Peter Dhassiah; Divya Shridhar M. Padinjattayil; VinithKumar N. Valsalan; Vijayakumaran Manambrakat; Sivakumar Dakshinamurthy; Sivaraman Thirunavukkarasu; Kirubagaran Ramalingam (Marine Biotechnology, 2015)

Salivary Alpha Amylase Activity in Human Beings of Different Age Groups Subjected to Psychological Stress - Gopal K. Sahu; Seema Upadhyay; Shradha M. Panna (Indian Journal of Clinical Biochemistry, 2014)

Unusual and rare manifestations of dengue during a dengue outbreak in a tertiary care hospital in South India - M. Neeraja; V. lakshmi; V. D. Teja; Vanjari Lavanya; E. N. Priyanka; K. Subhada; M. M. Parida; P. K. Dash; Sashi Sharma; P. V. L. Rao; Gopal Reddy (Archives of Virology, 2014)

Effect of Actin Polymerization Inhibitor During Oocyte Maturation on Parthenogenetic Embryo Development and Ploidy in Capra hircus - R. Ranjan; R. K. Singh; T. Yasotha; Manish Kumar; Gopal Puri; Kuldeep Kumar; Renu Singh; Sanjeev Bhure; D. Malakar; S. K. Bhanja; M. Sarkar; B. C. Das; et al. (Biochemical Genetics, 2013)

First report of an alphasatellite associated with Okra enation leaf curl virus - S. A. Chandran; R. M. Packialakshmi; K. Subhalakshmi; C. Prakash; K. Poovannan; A. Nixon Prabu; P. Gopal; R. Usha (Virus Genes, 2013)

Current state of knowledge regarding the world’s wetlands and their future under global climate change: a synthesis - Wolfgang J. Junk; Shuqing An; C. M. Finlayson; Brij Gopal; Jan Květ; Stephen A. Mitchell; William J. Mitsch; Richard D. Robarts (Aquatic Sciences, 2013)

Effect of mitotic inducers and retinoic acid blocker on expression of pluripotent genes in ES cells derived from early stage in vitro-produced embryos in buffalo - Ashok Kumar; Kuldeep Kumar; Renu Singh; Gopal Puri; R. Ranjan; T. Yasotha; R. K. Singh; M. Sarkar; Sadhan Bag (In Vitro Cellular & Developmental Biology - Animal, 2012)

Analysis of full-length sequences of two Citrus yellow mosaic badnavirus isolates infecting Citrus jambhiri (Rough Lemon) and Citrus sinensis L. Osbeck (Sweet Orange) from a nursery in India - A. M. Anthony Johnson; B. K. Borah; D. V. R. Sai Gopal; I. Dasgupta (Virus Genes, 2012)

A Comparison of the Temporally Integrated Monitoring of Ecosystems and Adirondack Long-Term Monitoring Programs in the Adirondack Mountain Region of New York - Kevin L. Civerolo; Karen M. Roy; John L. Stoddard; Gopal Sistla (Water, Air, & Soil Pollution, 2011)

Environmental variables and fisheries diversity of the Naaf River Estuary, Bangladesh - M. Shah Nawaz Chowdhury; M. Shahadat Hossain; Nani Gopal Das; Prabal Barua (Journal of Coastal Conservation, 2011)

Aboveground Characteristics, Yield Potential and Drought Tolerance in “Konyu” Potato Cultivars with Large Root Mass - T. Deguchi; T. Naya; P. Wangchuk; E. Itoh; M. Matsumoto; Xu Zheng; Jai Gopal; K. Iwama (Potato Research, 2010)

Influence of micronutrients on yeast growth and β-d-fructofuranosidase production - M. Venkateshwar; K. Chaitanya; Md. Altaf; E. J. Mahammad; Hameeda Bee; Gopal Reddy (Indian Journal of Microbiology, 2010)

Water quality assessment of Majhiaon block of Garwa district in Jharkhand with special focus on fluoride analysis - Kirti Avishek; Gopal Pathak; M. S. Nathawat; Usha Jha; Neeta Kumari (Environmental Monitoring and Assessment, 2010)

Association of a potyvirus with mosaic disease of gherkin (Cucumis anguria L.) in India - M. Srinivasulu; B. Sarovar; A. M. Anthony Johnson; D. V. R. Sai Gopal (Indian Journal of Microbiology, 2010)

Sequencing and computational analysis of complete genome sequences of Citrus yellow mosaic badna virus from acid lime and pummelo - Basanta K. Borah; A. M. Anthony Johnson; D. V. R. Sai Gopal; Indranil Dasgupta (Virus Genes, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Finite Element Method and GIS Based Distributed Model for Soil Erosion and Sediment Yield in a Watershed - M. Gopal Naik; E. P. Rao; T. I. Eldho (Water Resources Management, 2009)

A Confocal microscopic study on colony morphology and sporulation of Bacillus sp. - M. S. Mary; Judy Gopal; B. V. R. Tata; T. S. Rao; S. Vincent (World Journal of Microbiology and Biotechnology, 2008)

Skills of different mesoscale models over Indian region during monsoon season: Forecast errors - Someshwar Das; Raghavendra Ashrit; Gopal Raman Iyengar; Saji Mohandas; M. Das Gupta; John P. George; E. N. Rajagopal; Surya Kanti Dutta (Journal of Earth System Science, 2008)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Sodium-coupled Monocarboxylate Transporters in Normal Tissues and in Cancer - Vadivel Ganapathy; Muthusamy Thangaraju; Elangovan Gopal; Pamela M. Martin; Shiro Itagaki; Seiji Miyauchi; Puttur D. Prasad (The AAPS Journal, 2008)

Multi-criteria evaluation approach to GIS-based land-suitability classification for tilapia farming in Bangladesh - M. Shahadat Hossain; Sayedur Rahman Chowdhury; Nani Gopal Das; M. Moshiur Rahaman (Aquaculture International, 2007)

Sporulation and regeneration efficiency of phosphobacteria (Bacillus megaterium var phosphaticum) - M. Gomathy; M. Thangaraju; S. Gunasekaran; N. O. Gopal (Indian Journal of Microbiology, 2007)

Extraction of Multi-Class Pesticide Residues in Mango Fruits (Mangiferae indica L.): Application of Pesticide Residues in Monitoring of Mangoes - I. Mukherjee; S. Singh; P. K. Sharma; M. Jaya; M. Gopal; G. Kulshrsestha (Bulletin of Environmental Contamination and Toxicology, 2007)

Behavior of β-Cyfluthrin after Foliar Application on Chickpea (cicer aretinium L. ) and Pigeon Pea (cajanus cajan L.) - I. Mukherjee; M. Gopal; D. S. Mathur (Bulletin of Environmental Contamination and Toxicology, 2007)

Effect of bacteria isolated from composts and macrofauna on sorghum growth and mycorrhizal colonization - B. Hameeda; M. Srijana; O. P. Rupela; Gopal Reddy (World Journal of Microbiology and Biotechnology, 2007)

Distribution, use pattern and prospects for conservation of medicinal shrubs in Uttaranchal State, India - Bhupendra S. Adhikari; Mani M. Babu; Prem L. Saklani; Gopal S. Rawat (Journal of Mountain Science, 2007)

Transport of Nicotinate and Structurally Related Compounds by Human SMCT1 (SLC5A8) and Its Relevance to Drug Transport in the Mammalian Intestinal Tract - Elangovan Gopal; Seiji Miyauchi; Pamela M. Martin; Sudha Ananth; Penny Roon; Sylvia B. Smith; Vadivel Ganapathy (Pharmaceutical Research, 2007)

Antibacterial potential of γ-linolenic acid from Fischerella sp. colonizing Neem tree bark - Ravi K. Asthana; Arunima Srivastava; Arvind M. Kayastha; Gopal Nath; Sureshwar P. Singh (World Journal of Microbiology and Biotechnology, 2006)

In Vitro Detoxification of Pendimethalin by Two Actinomycetes spp - M. Gopal; S. K. Jha; L. Shukla; R. V. Rawat (Bulletin of Environmental Contamination and Toxicology, 2005)

Changes in verte brate‐type steroids and 5‐hydroxytryptamine during ovarian recrudescence in the Indian spiny lobster, Panulirus homarus - Ramalingam Kirubagaran; Dassiah M. Peter; Gopal Dharani; Nambali V. Vinithkumar; Gopinathapillai Sreeraj; Muthukamatchi Ravindran (New Zealand Journal of Marine and Freshwater Research, 2005)
Vertebrate‐type steroids (estradiol‐17β and progesterone) and 5‐hydroxytryptamine (5‐HT) were examined during the different stages of ovarian maturation in the Indian spiny lobster Panulirus homarus. Estradiol‐17β and progesterone in the haemolymph and ovary were quantified by radioim‐munoassay. Estradiol‐17β was not detectable in the haemolymph when the oocytes were in stage I. It appeared in the haemolymph only as the oocytes attained stage II. Subsequently, a sharp increase in the level of estradiol‐17β was observed in the haemolymph of lobsters with stage III oocytes; it then showed a significant fall when the ovary was full of stage IV oocytes. Although progesterone was also not detectable in the haemolymph when the oocytes were in stage I, it gradually increased during stages II and III and reached a peak level during stage IV. Surprisingly, both estradiol‐17β and progesterone were detectable in the ovary from stage I onwards. In the ovary, estradiol‐17β and progesterone showed peak levels during stages III and IV, respectively. A stage‐dependent change in the activity and distribution of 5‐hydroxytryptaminergic neurons in the brain and thoracic ganglia was also observed immunocytochemically in relation to ovarian recrudescence. Furthermore, HPLC‐EC conducted on the level of 5‐HT in the brain and thoracic ganglia indicated similar changes in relation to ovarian maturation. These results strongly suggest that 5‐HT is involved in ovarian development through certain inhibitory/stimulatory factors present in the X‐organ‐sinus gland complex of the eye‐stalk in the spiny lobster P. homarus.

Evaluation of Fentrazamide for Weed Control and Estimation of its Residues in Rice - I. Mukherjee; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 2005)

Disappearance of Chlorpyrifos from Cultures of Chlorella vulgaris - I. Mukherjee; M. Gopal; D. W. Dhar (Bulletin of Environmental Contamination and Toxicology, 2004)

Public Water Sources in Rural Watersheds of Nepal?s Middle Mountains: Issues and Constraints - Juerg Merz; Gopal Nakarmi; Smita Shrestha; Bed M. Dahal; Bhawani S. Dongol; Monika Schaffner; Sangeeta Shakya; Subodh Sharma; Rolf Weingartner (Environmental Management, 2004)

Residues of Pendimethalin after Weed Control in Cabbage Crop (Brassica oleracea var L. Capitata) - S. Arora; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 2004)

Persistence and Effectiveness of Iprodione Against Alternaria blight in Mustard - I. Mukherjee; M. Gopal; S. C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2003)

Molecular characterization of the tadpole shrimp Triops (Branchiopoda: Notostraca) from the Baja California Peninsula, México: New insights on species diversity and phylogeny of the genus - Gopal Murugan; Alejandro M. Maeda-Martínez; Hortencia Obregón-Barboza; Norma Y. Hernández-Saavedra (Hydrobiologia, 2002)

Evaluation of Residues of β-Cyfluthrin on Cotton - I. Mukherjee; M. Gopal; Not Available Not Available (Bulletin of Environmental Contamination and Toxicology, 2002)

Behaviour of β-Cyfluthrin and Imidacloprid in Mustard Crop: Alternative Insecticide for Aphid Control - M. Gopal; I. Mukherjee; S. Chander (Bulletin of Environmental Contamination and Toxicology, 2002)

Evaluating the Safety of β-Cyfluthrin Insecticide for Usage in Eggplant ( Solanum melongena L.) Crop - S. Sinha; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 2002)

Reproduction, molting, and growth of two Mexican uniparental forms of the tadpole shrimp Triops (Branchiopoda: Notostraca) under a recirculating culture system - Hortencia Obregón-Barboza; Alejandro M. Maeda-Martínez; Gopal Murugan (Hydrobiologia, 2001)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Soil Solarization: Technique for Decontamination of an Organophosphorus Pesticide from Soil and Nematode Control - M. Gopal; I. Mukherjee; D. Prasad; N. T. Yaduraju (Bulletin of Environmental Contamination and Toxicology, 2000)

Behavior of Different Formulations of Lindane on Chickpea - I. Mukherjee; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 1999)

Safety Evaluation of the Fungicide Iprodione on Cauliflower ( Brassica oleracea var. oleracea L.) - A. Datta; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Influence of Crystal Habit on Trimethoprim Suspension Formulation - Ashok K. Tiwary; Gopal M. Panpalia (Pharmaceutical Research, 1999)

Behavior of Lindane and Endosulfan on Cowpea - I. Mukherjee; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 1998)